ART THERAPY GROUP AS EFFORTS OF PSYCHIATRIC EMERGENCY PREVENTION - Irna Kartina (UNUSA Press, 2021)
World Health Organization (WHO) works hard for facing this covid-19 pandemic. The whole world applied WHO suggestions in public health actions, such as social distancing to reduce the spread of COVID-19. However, these protocols lead societies to feel isolated and lonely that increase stress and anxiety. Community service activities are one of the efforts that can be taken to empower family members to carry out simple therapy in reducing anxiety. This community service will focus on the mother who has a big influence on managing the family. This community service aimed to educate the mother’s group to help their family in improving knowledge and skill of emergency psychiatric prevention. This activity was divided into two main parts, a seminar about health education about Psychiatric Emergency and ran a workshop in the art therapy group. These community service results showed that health education can improve knowledge related to emergency psychiatric, and mothers could implement art drawing therapy as an effort of psychiatric emergency prevention. In conclusion, Art group therapy is recommended for the mother and her family to prevent the emergency psychiatric condition.